A CRISPR/Cas12a-based DNAzyme visualization system for rapid, non-electrically dependent detection of Bacillus anthracis. Issue 1 (31st December 2022) - Wang, Dongshu; Chen, Gang; Lyu, Yufei; Feng, Erling; Zhu, Li; Pan, Chao; Zhang, Weicai; Liu, Xiankai; Wang, Hengliang
ABSTRACT: As next-generation pathogen detection methods, CRISPR-Cas-based detection methods can perform single-nucleotide polymorphism (SNP) level detection with high sensitivity and good specificity. They do not require any particular equipment, which opens up new possibilities for the accurate detection and identification of Bacillus anthracis. In this study, we developed a complete detection system for B. anthracis based on Cas12a. We used two chromosomally located SNP targets and two plasmid targets to identify B. anthracis with high accuracy. The CR5 target is completely new. The entire detection process can be completed within 90 min without electrical power and with single-copy level sensitivity. We also developed an unaided-eye visualization system based on G4-DNAzyme for use with our CRISPR-Cas12a detection system. This visualization system has good prospects for deployment in field-based point-of-care detection. We used the antisense nucleic acid CatG4R as the detection probe, which showed stronger resistance to interference from components of the solution. CatG4R can also be designed as an RNA molecule for adaptation to Cas13a detection, thereby broadening the scope of the detection system.